2021
DOI: 10.1038/s41386-021-00989-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the brain structural connectome after a prospective randomized clinical trial of lithium and quetiapine treatment in youth with bipolar disorder

Abstract: The goals of the current study were to determine whether topological organization of brain structural networks is altered in youth with bipolar disorder, whether such alterations predict treatment outcomes, and whether they are normalized by treatment. Youth with bipolar disorder were randomized to double-blind treatment with quetiapine or lithium and assessed weekly. High-resolution MRI images were collected from children and adolescents with bipolar disorder who were experiencing a mixed or manic episode (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 72 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…The antipsychotic actions of quetiapine are likely derived from its antagonistic activity against DA D 2 receptors and serotonin 5-hydroxytryptamine 2 receptors [350]. Quetiapine is an atypical antipsychotic agent that is administered orally [351,352]. On occasion, it is recommended for the treatment of BD, although some studies have suggested that it is more successful specifically in alleviating the symptoms of anxiety and depression accompanying BD [351][352][353][354].…”
Section: Quetiapinementioning
confidence: 99%
See 1 more Smart Citation
“…The antipsychotic actions of quetiapine are likely derived from its antagonistic activity against DA D 2 receptors and serotonin 5-hydroxytryptamine 2 receptors [350]. Quetiapine is an atypical antipsychotic agent that is administered orally [351,352]. On occasion, it is recommended for the treatment of BD, although some studies have suggested that it is more successful specifically in alleviating the symptoms of anxiety and depression accompanying BD [351][352][353][354].…”
Section: Quetiapinementioning
confidence: 99%
“…Quetiapine is an atypical antipsychotic agent that is administered orally [351,352]. On occasion, it is recommended for the treatment of BD, although some studies have suggested that it is more successful specifically in alleviating the symptoms of anxiety and depression accompanying BD [351][352][353][354]. Five double-blind RCTs evaluated the tolerability and effectiveness of quetiapine over 8 weeks in BD patients who were undergoing a major depressive episode [350].…”
Section: Quetiapinementioning
confidence: 99%
“…The imaging mechanism of BD is still not clear, but many studies confirmed that BD might be related to neuroanatomical changes, distinct alterations in brain activity, and abnormal metabolism. Lei et al ( 20 ) studied the local anatomical traits of children with BD and found that they presented with an altered structural connector index (increasing cluster coefficient and characteristic path length), which normalized after treatment (lithium and quetiapine). Further, the authors found that the gray matter morphology index was 80% accurate in identifying the response of those children who had received treatment ( 20 ).…”
Section: Pathogenic Factorsmentioning
confidence: 99%
“…19 Though quetiapine and lithium exert effects via different mechanisms, there are few neuroimaging studies to understand their systems J o u r n a l P r e -p r o o f level impact on the brain connectome, their differences in location and timing of such effects, and their relation to treatment outcomes in vivo. 20,21 In adult patients with BD presenting with an acute manic episode, a resting-state fMRI study found that lithium treatment showed a more rapid normalization with respect to abnormal functional connectivity observed at baseline. 22 While pediatric connectome studies of drug effects in BD are limited, difference in regional effect of the antipsychotic risperidone and divalproex have been reported in children with BD presenting with an acute manic or mixed episode.…”
Section: Introductionmentioning
confidence: 99%